Corporate governance and CSR: fortress or loophole in the financial statement fraud? - Asri Nur Septiani; Etna Nur Afri Yuyetta (Jurnal Akademi Akuntansi)
Purpose: The impact of the audit committee, the board of commissioners, and corporate social responsibility on financial statement fraud is examined in this study. It examines the role of company size and profitability as control variables to provide a deeper understanding of the factors that shape fraudulent financial reporting.